Potential Diagnostic and Prognostic Value of Plasma Circulating MicroRNA-182 in Human Glioma - Xiao, Yilei (Med Sci Monit, 2016)
BACKGROUND: Previous studies showed the aberrant expression of microRNA-182 (miR-182) in glioma tissue. However, the exact role of circulating miR-182 in glioma remains unclear. Here, we confirmed the expression of plasma circulating miR-182 in glioma patients, and further explored its potential diagnostic and prognostic value. MATERIAL/METHODS: Real-time quantitative PCR (RT-PCR) was used to measure circulating cell-free miR-182 from 112 glioma patients and 54 healthy controls. RESULTS: Our findings showed that the level of circulating miR-182 in glioma patients was higher than that in healthy controls (P<0.001), which was significantly associated with KPS score (P=0.025) and WHO grade (P<0.001). The area under the receiver operating characteristic (ROC) curve (AUC) was 0.778. The optimal cut-off value was 1.56, and the sensitivity and specificity were 58.5% and 85.2%, respectively. Interestingly, a high predictive value of circulating miR-182 was observed in high-grade glioma (AUC=0.815). However, the AUC was lower in low-grade glioma (AUC=0.621). Kaplan-Meier analysis demonstrated that the cumulative 5-year overall survival rate in the high miR-182 group was significantly lower than that in the low miR-182 group in both overall survival (OS) (P=0.003) and disease-free survival (DFS) (P=0.006). Moreover, multivariate Cox analysis revealed that circulating miR-182 was an independent prognostic indicator for OS (P=0.034) and DFS (P=0.013). CONCLUSIONS: These results suggest that circulating miR-182 may be a potential noninvasive biomarker for the diagnosis and prognosis of human glioma.